Language Units Represent the National Flavor (Eurasian Research Bulletin, 2022)
This studies the relationship between language and culture is one of the topical areas of modern linguistics. Linguistic and regional studies aim to study the linguistic units that most clearly reflect the national characteristics of the culture of the people. Language as a way of exchanging information carries the national and cultural code of a particular people. There are words in it, the meaning of which a special part can be distinguished, reflecting the connection between language and culture, which is called the cultural component of the semantics of a language unit.